Solution‐Based Micro‐ and Nanoscale Metal Oxide Structures Formed by Direct Patterning for Electro‐Optical Applications - Yeh, Chun‐Cheng; Zan, Hsiao‐Wen; Soppera, Olivier (Advanced materials (Weinheim), 2018)
Due to their transparency and tunable electrical, optical, and magnetic properties, metal oxide thin films and structures have many applications in electro‐optical devices. In recent years, solution processing combined with direct‐patterning techniques such as micro‐/nanomolding, inkjet printing, e‐jet printing, e‐beam writing, and photopatterning has drawn much attention because of the inexpensive and simple fabrication process that avoids using capital‐intensive vacuum deposition systems and chemical etching. Furthermore, practical applications of solution direct‐patterning techniques with metal oxide structures are demonstrated in thin‐film transistors and biochemical sensors on a wide range of substrates. Since direct‐patterning techniques enable low‐cost fabrication of nanoscale metal oxide structures, these methods are expected to accelerate the development of nanoscale devices and systems based on metal oxide components in important application fields such as flexible electronics, the Internet of Things (IoT), and human health monitoring. Here, a review of the fabrication procedures, advantages, limitations, and applications of the main direct‐patterning methods for making metal oxide structures is presented. The goal is to highlight the examples with the most promising perspective from the recent literature. Solution‐based direct‐patterning (SDP) techniques are considered as low‐cost alternatives to conventional lithography for making micro‐ and nanoscale metal oxide patterns. Working mechanisms, patterning abilities, and limitations of different SDP techniques are discussed. In addition, functional devices fabricated by SDP techniques are presented, suggesting the potential of using SDP techniques for making high‐performance electro‐optical devices.